Red Piper Crocatum Leaves Extract Ethanol Lowering Malondialdehyde (MDA) and Blood Glucose Level In Hyperglycemic Wistar Rat - Sri Wahjuni; I Made Sukadana; dan Luh Putu Arisanti (Journal of Global Pharma Technology, 2017)
Changes in fast-food behavior became one cause of diabetes. Potential of the red betel leaf (Piper crocatum) can lower blood sugar levels allegedly because it contains antioxidant-potent compounds inductively induce certain organs to produce insulin hormones that play a role in lowering glucose levels in the blood.The aim of the study is to determine the effectiveness of Piper crocatum leaf ethanol extract in fixing the pancreas β-cell damage rate in alloxan induced hyperglycemic Wistar Rat. Methods: This study used randomized pre-and posttest control group design. Twenty-four (24) male Wistar rats divided into 6 groups namely P0 positive control (P0), P1 as a negative control (allowance 125 mg Kg -1BW), P2 (alloxan and extract dose 50 mgKg-1 BW), P3 (alloxan and extract dose 100 mg Kg -1 BW), P4 (alloxan and extract dose 150 mg Kg - 1 BW), P5 (alloxan and glibenclamide 0.18 mg/day 200g -1BW). Blood glucose measurement was taken through a vein tail performed by the glucose test method. Measurement of MDA levels, blood was taken from the jugular vein and analyzed by the TBARS method. The yield of Piper crocatum extraction with ethanol solvent was 13,1%.  The most significant results were shown by dosing of 150 mg Kg -1BW and extract of 50 mg Kg -1 BW gave a comparable effect to glibenclamide as a blood sugar-lowering drug. The results of phytochemical tests showed that Piper crocatum contains phenolic, alkaloid, and steroid. The results of GC-MS analysis of extracts active Piper crocatum were suspected to contain 29 compounds of 13 compounds known as phytol, neophytadiene, β-bisabolene, germacrene-D, α-humulene, sulfamethoxazole, caryophyllene, nandrolone phenylpropionate, thiamin, linalool, β-ocimene, Anthocyanin, and β-myrcene.Keyword: Red Piper crocatum leaf, Blood glucose, MDA (Malondialdehyde).